450 Retrospective Analysis of Surgical Clerk-Ins Within the Acute Receiving Unit: A Quality Improvement Project. (4th May 2021) - Lee, L; MacLeod, A; Bradley, A
Abstract: Introduction: Accurate patient documentation at the ARU is vital to patient safety and ensuring smooth handovers to secondary care services. Because the nature of surgical treatment requires frequent patient handovers, and this increases the risk of miscommunication, we aimed to assess the quality of surgical clerk-ins and identify areas for improvement. Method: Emergency admissions at the Dumfries Galloway Royal Infirmary were audited, looking at documentation quality under various clerk-in sections. Data was analysed before presentation to clinical governance. Results: When 46 patient clerk-ins were examined, venous thromboembolism (VTE) prophylaxis plans were performed in only 24% of admissions - less than 1 in 4 patients. Comparing out-of-hours and in-hours patient documentation, much higher omission rates were identified in the out-of-hours documentation: in systemic enquiry (42 vs 100%) and family history (31% vs 66%). Conclusions: These results brought to attention the effect of hospital admission timing on patient documentation quality, and the lack of VTE prophylaxis planning. In surgery, these plans are key to minimising risk of avoidable thromboembolic complications. A departmental meeting was convened to stress the importance of accurate and comprehensive clerk-ins to ARU doctors. Future audits could explore the factors influencing documentation quality for out-of-hours admissions, and ways to address these issues.